A hybrid SEM/ANN analysis to understand youtube video content's influence on university students' eLearning acceptance behavior - Phan Cong Thao Tien; Tran Thien Phuc; Nguyen Thi Hai Binh (Proceedings of the National Conference in Education and Commerce, 2023)
A hybrid analysis of Structural Equation Modeling (SEM), Artificial Neural Network (ANN), and Importance- Performance Map Analysis (IPMA) was used to examine how YouTube videos affect university students' acceptance in Ho Chi Minh City (HCMC). Performance expectation was the most important component by both ANN and IPMA assessments, and theoretically, the presented model gave several explanations for the effect of individual determinants of desire to utilize eLearning from Internet services. The findings support earlier research showing performance and effort expectations strongly impact eLearning adoption. The report encouraged academics in HCMC to utilize YouTube. Respondents wanted to employ modern technologies in their teaching. UTAUT and TAM were used to discuss the findings.
Keywords: 330; Social media; YouTube; Higher education; eLearning; Ho Chi Minh City's students; TAM; UTAUT